Judaism in late antiquity. - Neusner, Jacob, 1932-; Avery-Peck, Alan J. 1953-; Chilton, Bruce. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1994)
These two volumes introduce the sources of Judaism in late antiquity to scholars in adjacent fields, such as the study of the Old and New Testaments, ancient history of Classical Antiquity, earliest Christianity, the ancient Near East, and the history of religion. Here, in two volumes, leading American, Israeli, and European specialists in the history, literature, theology, and archaeology of Judaism offer factual answers to the two questions that the study of any religion in ancient times must raise. The first is, what are the sources - written and in material culture - that inform us about that religion? The second is, how do we understand those sources in the reconstruction of the history of various Judaic systems in antiquity. The chapters set forth in simple statements, intelligible for non-specialists, the facts the sources provide. Because of the nature of the subject and acute interest in it, we also raise some questions particular to the study of Judaism, those dealing with its historical relationship with nascent Christianity in New Testament times. The work forms the starting point for the study of all the principal questions concerning Judaism in late antiquity and sets forth the most current, critical results of scholarship.